Maxillary anomalies in choanal atresia: a case report - Merheb Marie; Devoti Jean François; Simon Etienne; Brix Muriel (EDP Sciences, 2024)
Choanal atresia is defined as the complete obstruction of the posterior nasal airway. The obstruction is the origin of maxillary impairment in the development. We describe a case of a man with unilateral choanal atresia who was referred to the maxilla-facial surgery department for his maxillary anomalies. The patient suffered from hypoplasia of the midface with class III malocclusion. and retromaxillia. He had also solitary median maxillary central incisor syndrome (SMMCI). Choanal atresia leads to nasal obstruction resulting in mouth breathing. The maxillary consequences are long face, contraction of the upper dental arch and high arched palate. The patients present class III malocclusion with posterior cross bite, anterior open bite. SMMCI may also be present. The maxillary anomalies would be only slightly due to the presence of chronic nasal obstruction. The mouth breathing, which results from the nasal obstruction, is an etiological factor at the origin of maxillary anomalies.